1999
DOI: 10.1074/jbc.274.41.29536
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the NH2- and COOH-terminal Domains of the Inhibitory Region of Troponin I in the Regulation of Skeletal Muscle Contraction

Abstract: The role of the inhibitory region of troponin (Tn) I in the regulation of skeletal muscle contraction was studied with three deletion mutants of its inhibitory region: 1) complete (TnI-(⌬96 -116)), 2) the COOH-terminal domain (TnI-(⌬105-115)), and 3) the NH 2 -terminal domain (TnI-(⌬95-106)). Measurements of Ca 2؉ -regulated force and relaxation were performed in skinned skeletal muscle fibers whose endogenous TnI (along with TnT and TnC) was displaced with high concentrations of added troponin T. Reconstituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…1). Also, results from our laboratory using mutants of skeletal TnI suggest that residues 105-115 of the inhibitory region (comparable to residues 137-147 of HCTnI) are much more critical for the biological activity of TnI than residues 96 -106 (39). From this standpoint, a significant amino acid change in this region could definitely affect mechanisms of cardiac muscle contraction.…”
Section: Discussionmentioning
confidence: 98%
“…1). Also, results from our laboratory using mutants of skeletal TnI suggest that residues 105-115 of the inhibitory region (comparable to residues 137-147 of HCTnI) are much more critical for the biological activity of TnI than residues 96 -106 (39). From this standpoint, a significant amino acid change in this region could definitely affect mechanisms of cardiac muscle contraction.…”
Section: Discussionmentioning
confidence: 98%
“…It is likely that these segments undergo structural transitions that are driven by Ca 2C binding to the regulatory head and are likely to be dependent on the structural context. NMR studies of peptides from the central inhibitory region (I p ) of skeletal TnI, which alone can inhibit acto-myosin ATPase, summarized by Szczesna et al, 29 have revealed an extended, bent structure: residues 104-115 formed an amphiphilic helix-like structure, bent around two central proline residues, 30 while the longer 96-115 sequence appeared largely non-helical with a kink at Gly104. 31 It has also been noted 32 that I p shows sequence homology to an actin-binding loop in profilin, an actin-binding protein.…”
Section: -4 Eachmentioning
confidence: 99%
“…However, the presence of ssTnI instead of cTnI resulted in a decrease in the cooperativity of force development that was statistically significant (p Ͻ 0.05) when cTnT4 was utilized (Table I). Although the molecular mechanism of cooperativity is still not clearly understood, the Ca 2ϩ dependence of muscle contraction is known to be highly cooperative with Hill coefficients ranging from 1 to 4 depending on the system used (33)(34)(35). Biochemical studies on fast skeletal TnT (fsTnT) peptides suggest that part of its N-terminal region (residues 70 -159, corresponding to residues 102-189 of cTnT3) promotes cooperative interactions between functional units (36,37).…”
Section: ϫ015) Than Intact Fibers Similar To What Has Been Reported mentioning
confidence: 99%